Eco-friendly mass production of poly(p-phenylenediamine)/graphene oxide nanoplatelet composites and their electrorheological characteristics. (18th January 2016) - Cao, Yanlin; Choi, Hyoung Jin; Zhang, Wen Ling; Wang, Baoxiang; Hao, Chuncheng; Liu, Jingquan
Abstract: Poly(p-phenylenediamine)/graphene oxide nanoplatelet (PPDA/GONP) composites were synthesized via in situ oxidation polymerization of p-phenylenediamine (PDA) in graphene oxide nanoplatelets (GONPs) suspension for potential electrorheological (ER) fluid applications. Initially, the mass production of GONPs can be achieved through a simple and green ball milling process of graphite with dry ice. The versatile synthesis methods and multifunctionality of poly(p-phenylenediamine) (PPDA) enable the wide potential applications of PPDA/GONP composites. The π−π stacking interaction between GONP and PDA is a key factor to fabricate PPDA/GONP composite successfully. The ER characteristics of both PPDA/GONP composites and PPDA in silicone oil medium were examined using a rotational rheometer equipped with a high voltage generator. The resultant PPDA/GONP composites exhibited improved typical ER behavior compared with that of pure PPDA, providing a new potential application of the PPDA/GONP composites as an intelligent material.